2010
DOI: 10.1589/jpts.22.61
|View full text |Cite
|
Sign up to set email alerts
|

Isolation Frequency and Antimicrobial Susceptibility of Bacterial Pathogens Isolated from Physical Therapeutic Instruments in General Hospitals

Abstract: Abstract.[Purpose] As demands for physical therapy increase, the numbers of patients in physical therapy rooms are rapidly increasing. However, studies on the state of microorganism infections of physical therapy equipment and their effects on hospital-acquired infections are currently lacking. The purpose of this study was to examine the rate of infections of physical therapy rooms by pathogenic microorganisms.[Methods] Facilities in physical therapy rooms were divided into three groups, therapeutic environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
4
7
0
Order By: Relevance
“…In the present study, the predominant Gramnegative bacilli, Acinetobacter sp. displayed the highest resistance to two commonly used antibiotics, such as ceftriaxone and ampicillin and are more or less comparable to the results of a prior study [30]. Especially, the isolates of Acinetobacter were found to be susceptible to amikacin.…”
Section: Antibiogramsupporting
confidence: 77%
See 1 more Smart Citation
“…In the present study, the predominant Gramnegative bacilli, Acinetobacter sp. displayed the highest resistance to two commonly used antibiotics, such as ceftriaxone and ampicillin and are more or less comparable to the results of a prior study [30]. Especially, the isolates of Acinetobacter were found to be susceptible to amikacin.…”
Section: Antibiogramsupporting
confidence: 77%
“…Earlier it was reported that Acinetobacter sp. is the main Gram-negative bacilli isolated from therapeutic equipments of hospital settings [28,30]. In contrast, some other studies described that E. coli was the most common Gram-negative bacteria isolated from medical equipments and hospital environment [14,20,23], whereas another study described that Enterobacter sp.…”
Section: Diversity Of Bacterial Isolatesmentioning
confidence: 99%
“…Likewise, most E. faecium isolates were resistant to ampicillin and tetracycline, and were sensitive to imipenem, nitrofurantoin and teicoplanin like those of E. faecalis isolates. E. faecalis and E. faecium isolates showed VanB phenotype which is resistant to vancomycin but sensitive to teicoplanin were 58% and 25%, respectively (Table 2), (Kim et al, 2010b). All of Staphylococcus spp.…”
Section: Emergence Of Vancomycin-resistant Pathogenmentioning
confidence: 98%
“…Their genomic DNAs were extracted using an Accuprep genomic DNA extraction kit (Bioneer, Korea). PCR using 16S rRNA primer sets was conducted as described previously (Kim et al, 2010b). After electrophoresis on agarose gels, individual amplified products were purified using an Accuprep gel purification kit (Bioneer, Korea).…”
Section: Bacterial Isolation and Identificationmentioning
confidence: 99%
See 1 more Smart Citation